2010
DOI: 10.1016/j.bpc.2010.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Human serum albumin binding ibuprofen: A 3D description of the unfolding pathway in urea

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. A C C E P T E D M A N U S C R I P T ACCEPTED MANU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
34
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 57 publications
9
34
0
Order By: Relevance
“…By using ab initio and rigid body modeling (Svergun, 1999;Chacón et al, 2000;Heller et al, 2003), the shape of monomeric forms, the multimeric state of proteins, and protein complexes can be assessed (Putnam et al, 2007;Mertens and Svergun, 2010;Nogales et al, 2010;Pons et al, 2010). In addi- tion, SAXS allows the quantitative analysis of flexible systems including multidomain and intrinsically unfolded proteins (Bernadó et al, 2005), mechanisms of denaturation and unfolding (Segel et al, 1998;Galantini et al, 2008;Leggio et al, 2009), the stabilizing role of the ligands in denaturating conditions (Galantini et al, 2010), and molecular mechanisms of ligand release (Tabarani et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…By using ab initio and rigid body modeling (Svergun, 1999;Chacón et al, 2000;Heller et al, 2003), the shape of monomeric forms, the multimeric state of proteins, and protein complexes can be assessed (Putnam et al, 2007;Mertens and Svergun, 2010;Nogales et al, 2010;Pons et al, 2010). In addi- tion, SAXS allows the quantitative analysis of flexible systems including multidomain and intrinsically unfolded proteins (Bernadó et al, 2005), mechanisms of denaturation and unfolding (Segel et al, 1998;Galantini et al, 2008;Leggio et al, 2009), the stabilizing role of the ligands in denaturating conditions (Galantini et al, 2010), and molecular mechanisms of ligand release (Tabarani et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The inside wall of the pocket is formed by hydrophobic side chains, whereas the entrance to the cavity is surrounded by positively charged residues. The exceptional feature of this site is the binding of the ligand, which is a bulky heterocyclic anion with a negative charge localized in the middle of the molecule [48]. Ligands binding in site I include warfarin, phenylbutazone, and azapropazone.…”
Section: Site-specific Probementioning
confidence: 99%
“…In an investigation of the stabilizing effect of ibuprofen in the unfolding of HSA induced by urea, Galantini et al reported that domain I, which contains polar residues, is capable of participating in electrostatic interactions with ibuprofen, an arylpropionic acid nonsteroidal anti-inflammatory drug that is similar to KP (26). Hence, in this study, we attempted to clarify the mechanism for the effect of allosteric binding from the perspective of an N-B transition.…”
Section: Introductionmentioning
confidence: 98%